PELATIHAN BERWIRAUSAHA SESUAI SYARIAH BAGI REMAJA PELAKU USAHA KREATIF DI KOTA PEKANBARU - Elisanovi, Elisanovi; Lusiawati, Lusiawati; Syafei, Jasmina; Mukhlis, Faiza; Novius, Andri (STIE Pelita Nusantara, 2022)
Translator The purpose of this community service activity is to provide understanding to Muslim youth who become entrepreneurs so that they can carry out business practices in accordance with sharia. In addition, universities can contribute to entrepreneurship, especially for Muslim youth in accordance with sharia principles. The method used in this activity is in the form of training with the provision of material and questions and answers regarding the application of sharia principles in all business activities they are currently undergoing and motivating the entrepreneurial spirit that is not only looking for worldly profits but also oriented to the hereafter. The results expected that these young Muslim creative economy can see the potential of the sharia economy with products and management or manage businesses in accordance with sharia principles so that they are able to compete in the sharia economy.Keyword: Entrepreneur, Sharia